The Role of Metadata in the Infrastructure for Archival Interoperation. Issue 11 (November 2014) - Simons, Gary F.
Abstract Sociolinguists want to be able to share and compare datasets, and they want to do so now and far into the future. Achieving this dream will require that sociolinguistic corpora are archived in a sustainable way and that those corpora are encoded in such a way that interoperation among them is possible. This paper first sets the stage by describing broadly the requirements for sustainable archiving. It then focuses on the role of metadata in constructing an infrastructure that will support the kind of interoperation that is envisioned – both corpus‐level metadata for facilitating the discovery of relevant corpora and observation‐level metadata for facilitating the comparison of observations that are comparable.